2020
DOI: 10.1038/s41419-020-2565-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NLRP3-inflammasome prevents cognitive deficits in experimental autoimmune encephalomyelitis mice via the alteration of astrocyte phenotype

Abstract: Multiple sclerosis (MS) is a chronic disease that is characterized by demyelination and axonal damage in the central nervous system. Cognitive deficits are recognized as one of the features of MS, and these deficits affect the patients' quality of life. Increasing evidence from experimental autoimmune encephalomyelitis (EAE), the animal model of MS, has suggested that EAE mice exhibit hippocampal impairment and cognitive deficits. However, the underlying mechanisms are still unclear. The NLRP3 inflammasome is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(84 citation statements)
references
References 66 publications
5
78
1
Order By: Relevance
“…Of notice, inflammasome activation has been associated with cognitive symptoms in several human diseases ( 18 ) and with cognitive deficits in autoimmune experimental models ( 19 ). As such, we further investigated inflammasome activation as a possible mechanism behind the low-grade inflammation observed and the cognitive deterioration.…”
Section: Resultsmentioning
confidence: 99%
“…Of notice, inflammasome activation has been associated with cognitive symptoms in several human diseases ( 18 ) and with cognitive deficits in autoimmune experimental models ( 19 ). As such, we further investigated inflammasome activation as a possible mechanism behind the low-grade inflammation observed and the cognitive deterioration.…”
Section: Resultsmentioning
confidence: 99%
“… 245 NLRP3 inhibition with MCC950 was shown to significantly suppress IL-1β production and airway inflammation in the lungs of mice with cystic fibrosis 246 and to prevent cognitive deficits in mice with experimental autoimmune encephalomyelitis (EAE). 247 However, recent studies have shown that MCC950/CRID3 targets wild-type NLRP3 but not NLRP3 gain-of-function point mutants related to CAPS. 248 The CFTR (inh) -172 analog CY-09 also inhibits NLRP3 ATPase activity by directly binding to the ATP-binding motif of the NLRP3 NACHT domain.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recent landmark studies have allowed the characterization of a population of neurotoxic astrocytes expressing complement component 3 (C3) in response to pro-inflammatory cytokines released by activated microglia [ 9 ]. This subset of reactive astrocytes, termed A1, exhibit transcriptional programs destructive to synapses and oligodendrocytes and inhibitory to remyelination with potential pathogenic consequences in human MS and animal models of the disease [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%